Development of a Book on Home Civilization Based on Project Based Learning (PjBL) to Foster Broadminded Character - Putri, Brigita Sherlyta Erlansa; Nugrahanta, Gregorius Ari Nugrahanta (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Broadminded character is understood by one's ability to know oneself, make decisions, analyze patterns, be broadminded, contribute positively, empathize, know one's limits, capture the essence of the problem, have self-awareness, become a reference for opinions, and have integrity. Bullying often occurs in the world of education, which reflects a lack of wisdom in behaviour. The rise of bullying cases requires in-depth education to form a broadminded character. This study aims to develop a textbook on home civilization based on PjBL to foster broadminded character. This study used the ADDIE-type Research & Development (R&D) method. Ten certified elementary school teachers were involved in conducting a needs analysis, five teachers and five experts as expert judgment validators and eight children aged 10-12 years were involved in a limited trial of the book. The results showed that 1) the book on PjBL-based home civilization to foster broadminded character was developed with ADDIE stages; 2) the quality of the textbook was classified as "very good" so that it did not require revision (3.89 on a scale of 1-4); 3) the application of this textbook had a significant effect on broadminded character (p < 0.05) with a category effect (r = 0.992) or equivalent to 98% which was classified as a "large" effect category. The level of effectiveness is high (89.61%).